Alectinib versus crizotinib in treatment-naive anaplastic lymphoma kinase-positive (ALK+) non-small-cell lung cancer: CNS efficacy results from the ALEX study. (12th September 2018) - Gadgeel, S; Peters, S; Mok, T; Shaw, A T; Kim, D W; Ou, S I; Pérol, M; Wrona, A; Novello, S; Rosell, R; Zeaiter, A; Liu, T; et al.
Abstract: Background: The phase III ALEX study in patients with treatment-naive advanced anaplastic lymphoma kinase mutation-positive ( ALK +) non-small-cell lung cancer (NSCLC) met its primary end point of improved progression-free survival (PFS) with alectinib versus crizotinib. Here, we present detailed central nervous system (CNS) efficacy data from ALEX. Patients and methods: Overall, 303 patients aged ≥18 years underwent 1:1 randomization to receive twice-daily doses of alectinib 600 mg or crizotinib 250 mg. Brain imaging was conducted in all patients at baseline and every subsequent 8 weeks. End points (analyzed by subgroup: patients with/without baseline CNS metastases; patients with/without prior radiotherapy) included PFS, CNS objective response rate (ORR), and time to CNS progression. Results: In total, 122 patients had Independent Review Committee-assessed baseline CNS metastases (alectinib, n  =   64; crizotinib, n  =   58), 43 had measurable lesions (alectinib, n  =   21; crizotinib, n  =   22), and 46 had received prior radiotherapy (alectinib, n  =   25; crizotinib, n  =   21). Investigator-assessed PFS with alectinib was consistent between patients with baseline CNS metastases [hazard ratio (HR) 0.40, 95% confidence interval (CI): 0.25–0.64] and those without (HR 0.51, 95% CI: 0.33–0.80, P interaction = 0.36). Similar results were seen in patients regardless of prior radiotherapy. Time to CNS progression was significantly longer with alectinib versus crizotinib and comparable between patients with and without baseline CNS metastases ( P  <   0.0001). CNS ORR was 85.7% with alectinib versus 71.4% with crizotinib in patients who received prior radiotherapy and 78.6% versus 40.0%, respectively, in those who had not. Conclusion: Alectinib demonstrated superior CNS activity and significantly delayed CNS progression versus crizotinib in patients with previously untreated, advanced ALK + NSCLC, irrespective of prior CNS disease or radiotherapy. Clinical trial registration: ClinicalTrials.gov NCT02075840